(untitled) (Archive of Conferences, 2022)
The Research Proposal prepared for the Master’s Dissertation at the Worlds Languages University of Uzbekistan in the field of Linguistics. This Proposal summarize the ideas about word formation in Uzbek and English lexicology, the attitude to word formation and related theoretical views, processes of word formation are bases upon which words are formed in languages. Firstly, the paper introduces the term word formation along with a few previous studies. Secondly, processes of word constructions are discussed then processes are compared. Finally, certain conclusions, as well as some further areas of research are proposed.